Micro-teaching course: Does it affect students' teaching ability? - Muluk, Safrul; Habiburrahim, Habiburrahim; Ardiansyah, Ardiansyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This explanatory quantitative study aimed to identify the correlation between the students’ Micro Teaching and Field Pre-Service Teaching courses. The population of the study was the students of the English Education Department of the Faculty of Education and Teacher Training Universitas Islam Negeri (UIN) Ar-Raniry, Banda Aceh, Aceh, Indonesia who had taken the micro-teaching class and had conducted field pre-service teaching, a total of 141 students. Then, 43 students were selected as the sample of this study. Data came from these students’ scores in Micro Teaching class and Field Pre-Service Teaching. The data were analyzed by using Pearson Product Moment with the SPSS 16.0. The findings indicated that there was no significant correlation between micro-teaching and field pre-service teaching (p-value = .196; p>.05). In addition, the strength level of the Pearson correlation coefficient between the two variables was negative and weak (r = -0.201). It can be interpreted that the students’ teaching ability was not dependent upon their micro-teaching scores.